1977
DOI: 10.1111/j.1467-842x.1977.tb01359.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of Australian smokers and nonsmokers

Abstract: The 1983 National Dietary Survey of Adults and the 1983 Risk Factor Prevalence Survey No. 2, conducted on the same subjects, provided an opportunity to examine the nutrient intakes of smokers (1024 men and 785 women) and nonsmokers (1974 men and 2421 women). The nutrients analysed were energy (kJ); fat (g/day and contribution to energy); starch (contribution to energy); dietary fibre (g/day and g/1000 kJ); alcohol (g/1000 kJ); polpnsaturated/saturated fats ratio; cholesterol, niacin, viramin C, calcium, iron, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
2
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
2
5
2
2
Order By: Relevance
“…An Australian study reported significantly lower intakes of phosphorus and Mg in mg/day in smokers. 19 A study from Italy reported no difference in K intake between smokers and nonsmokers. 21 In INTERMAP, smokers consumed significantly less phosphorus than never smokers for Japanese men and women and UK and US men, while UK and US women who smoked reported nonsignificantly lower intakes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…An Australian study reported significantly lower intakes of phosphorus and Mg in mg/day in smokers. 19 A study from Italy reported no difference in K intake between smokers and nonsmokers. 21 In INTERMAP, smokers consumed significantly less phosphorus than never smokers for Japanese men and women and UK and US men, while UK and US women who smoked reported nonsignificantly lower intakes.…”
Section: Discussionmentioning
confidence: 97%
“…Nutrient intakes not included in the metaanalysis that have often been found to differ between smokers and nonsmokers include higher intakes of MUFA, 1,2,5,6,9,10,22,27,34,39,46 lower vitamin A intake, 1,2,5,20,35,36,42,43,45 lower thiamine intake, 1,2,16,19,21,42,45 and lower PFA/ SFA. 15,21,22,26,28,29,31,[37][38][39]46 In INTERMAP, MUFA intake was higher in smokers than never smokers for UK and US women; vitamin A intake was significantly lower for US men and women; thiamine intake was significantly lower for US men and women, the only gender-country subgroups for which it was available; and PFA/SFA was significantly lower in smokers in UK and US men and women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yapılan birçok araştırmada, sigara içen bireylerin, sebze ve meyveleri daha seyrek ve/veya daha az miktarlarda tükettikleri sonucuna varılmıştır. 1,17,[21][22][23][24] Zondervan ve ark. tarafından yapılan çalışmada da sigara içen kadınların düşük dü-zeyde meyve tükettikleri saptanmıştır.…”
Section: Discussionunclassified
“…Sigara içen ve içmeyen bireylerin günlük aldıkları enerji ve besin öğelerinin miktarlarını araştıran birçok çalışmada farklı sonuçlar elde edilmiştir. 1,16,[22][23][24]32,33 Ancak bu araştırmalardaki en önemli ortak sonuç, sigara içen bireylerin günlük tükettikleri C vitamini miktarının, sigara içmeyenlere göre daha düşük olmasıdır. Çalışmamızda sigara içen bireyler, içmeyenlere göre daha az sebze ve meyve tü-ketmekte, bunun sonucu daha az C vitamini ve diğer antioksidan besin öğelerini almaktadır.…”
Section: Discussionunclassified